Science Communication as Praxis: Analysis of ‘The Periodic Table’ by Primo Levi - Luciana Massi; Guilherme da Silva Lima (Substantia)
This article is an analysis of the book “The Periodic Table”, which derives from Primo Levi’s praxis. This is an attempt to highlight the reason for the communicative practice and subject-object relationship involved in his book’s production. The analysis was based on both praxis categories and the subject/object opposition unit emerging from historical and dialectical materialism. Accordingly, we mobilize and advocate for a science communication concept based on the sense of praxis that is not limited to the discursive aspects of this production type. Based on the sources’ selection carried out in the collection of “Centro Internazionale di Studi Primo Levi”, this book can be the very result of Levi’s transformative praxis, which was driven by a liberating human formation substantiated by science. Science outspread as transformative praxis in Primo Levi’s work and in the subject/object relationship observed it. Human development was the reason for his practice, and it was driven by a liberating perspective, by outspreading a science that could help expanding the concept of world and society. This reason is linked to his biography and activities, which play a potential humanizing role in relationships man set with nature and society. The present article sought to broaden the understanding of SC as praxis based on a case study and to stand against a narrow view of SC and the superficial reasons often linked to it.